Influence of the carbon fiber plate curvature of advanced footwear technology on the running energetic cost and 3000-m performance - Ruiz-Alias, S. A.; Pérez-Castilla, A.; Soto-Hermoso, V. M.; Garcia-Pinillos, F. (Sports Engineering, 2024)
This study aimed to explore the effect of two similar commercialized advanced footwear technology models differing mainly in their plate geometry (i.e., low and high curvature plate) on the running energetic cost in both non-fatigued and fatigued states. It also sought to determine their impacts on 3000-m performance. Twelve highly trained male athletes performed four 5-min trials (two advanced technology models, two trials). In each experimental session, athletes completed a 3000-m trial which was followed by a 5-min trial to test the running energetic cost when fatigued. Athletes exhibited a lower running energetic cost when wearing the low curvature plate in a non-fatigued state (P = 0.034; - 1.13 [- 1.92 to - 0.11] %), which persisted with better performance in the 3000-m trial (P = 0.017; - 0.42 [- 0.74 to - 0.09] %). However, in a fatigued state, non-significant differences were reported (P = 0.207). The low curvature plate seems to be more effective than the high curvature plate when running at low intensity in a fresh state as well as in a maximal high-intensity effort. However, non-significant differences between plate geometries were observed when fatigue was increased.